a comprehensive approach to institutionalize business innova - "Gupta, Praveen" (New Delhi, 2008)
"Part 1 : Evolving innovation - Chapter 1 : history of innovation - history and evolution of knowledge: from stone daggers to metal , history and evolution of knowledge: language, numerals and art, evolutionary timeline, the world of innovation, great innovators: from Galileo to Edison, national innovation initiatives, understanding innovation models, knowledge innovation, institutionalizing innovation -- Chapter 2 : creativity and innovation -- definition of creativity and its components, why creativity is essential, some creativity myths, fostering creativity, what it takes to be creative, study -- collisions --bravery -- tools -- experience -- improvisation -- play -- eve of destruction? -- creativity to innovation -- practical exercise -- cases -- Chapter 3 : the conventional tools of creativity -- becoming creative -- cause and effect -- the oscar and felix approach to creativity -- letting go: waking up oscar -- structured tools of creativity -- developing creative focus -- styles of creativity -- exercising your mind -- simple mind expanders -- medium difficulty mind expenders -- advanced mind expanding exercises -- setting directions : understanding the context, manager-to-manager event -- possibility generator -- exaggerate objectives -- selection window -- suspending rules : gaining new insights, say / think -- role play -- cartoon drawing -- listening for comprehension -- thinking differently: shattering paradigms -- brain storming -- the six thinking hats -- free association -- establishing formatted work spaces : unleashing the value of surroundings -- force analysis -- card sort / affinity diagram -- mind mapping -- environment -- stimulating mechanisms : focusing energy -- five why's -- thinking words: creates method -- utilizing experiences -- reality matrix -- presentation -- Chapter 4 : Innovation in the information age -- Chapter 5 : need for innovation on demand -- Part 2 : Understanding innovation -- Chapter 6 : brain hardware and innovation processes -- Chapter 7 : framework for innovation -- Chapter 8 : Room for innovation -- Chapter 9 : Innovation deployment -- Chapter 10 : Measures of innovation -- Part 3 : Institutionalizing innovation -- Chapter 11 : Innovation in services -- Chapter 12 : Protecting the innovation -- Chapter 13 : Commercializing the innovation -- Chapter 14 : Managing innovation -- Final thoughts: wisdom of innovation."
includes bibliographical references and index
Keywords: "Research, Industrial--Management"; Technological innovations--Management